OntoPart: at the cross-roads of ontology partitioning and scalable ontology alignment systems. (1st January 2013) - Kachroudi, Marouen; Zghal, Sami; Ben Yahia, Sadok
In the semantic web register, ontologies are the cornerstones for many applications thanks to their expressiveness ability to explicate shared conceptualisations. Neverthless, the steady growth of these ontologies made their management beyond human capabilities. Thus, ontology partitioning seems to be a thriving issue for tackling such oversized ontologies and their administration through several systems. In this respect, ontology alignment task is an important component of the integration systems by providing a solution for data heterogeneousness by allowing their interoperability. In addition, such used alignment techniques implement complex computations that are losing their effectiveness against the scalability problem. To meet this challenge, we introduce in this paper a partitioning method, designed to take into account the goal of the alignment task. This method allows to split both ontologies to be aligned in two reduced size block sets, containing the elements capable to be matched. The results of tests performed with our method on different pairs of ontologies show their effectiveness.